1952
DOI: 10.1002/ange.19520641104
|View full text |Cite
|
Sign up to set email alerts
|

Über den Feinbau einiger Proteine

Abstract: Indikationsgebietes, da die im LuminaI ruhende spasmolytische Wirkung seine Anwendung be] der Epilepsie erlaubte. Durch die Mitarbeitcr Horleins konnte in spateren Jahren die Palette der Barbiturssuren noch einmal dtirch das Phanodorm, Prominal und Evipan erweitert werden, von denen das letztere durch seine Anwendbarkeit als intravenoses Kurznarkotikum wieder einen neuen Anfangspunkt einer Entwicklung darstellt.Inzwischen war die Personlichkeit Horleins weit uber die eines wissenschaftlichen Chemikers hinausge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1954
1954
1967
1967

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Early studies of silk revealed the presence of filamentous material, and estimates of their lateral dimension have ranged from 40-300 A (18). In particular, Zahn (20) suggested that the filamentous material consisted of microfibrils 40-80 A wide. In most instances the methods of preparation or examination would have precluded the recognition of a highly asymmetric cross-sectional shape in the microfibril.…”
Section: Bombyx Mori Fibroinmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies of silk revealed the presence of filamentous material, and estimates of their lateral dimension have ranged from 40-300 A (18). In particular, Zahn (20) suggested that the filamentous material consisted of microfibrils 40-80 A wide. In most instances the methods of preparation or examination would have precluded the recognition of a highly asymmetric cross-sectional shape in the microfibril.…”
Section: Bombyx Mori Fibroinmentioning
confidence: 99%
“…1 and 2. A lateral alternation of crystalline and amorphous material of this type is favored by Z a h n (20) and would account for such properties as the anisotropic swelling during water sorption (7).…”
Section: Bombyx Mori Fibroinmentioning
confidence: 99%
See 1 more Smart Citation